Peran Guru Balai Pengajian Ummi Gampong Aree Kecamatan Delima Kabupaten Pidie - Hayati, Cut Intan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IAIN Lhokseumawe, 2022)
This study aims to determine the extent of the role of teachers at the Ummi Gampong Aree Study Center, Delima District, in the spiritual development of adolescents and to identify the challenges they face. The research adopts a qualitative approach. Data collection techniques used include observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and drawing conclusions. The results show that teachers employ various teaching methods such as lectures, Q&A sessions, practice, and disciplinary actions to shape the personality and spirituality of the adolescents. The teaching materials include the sciences of Tawhid, Fiqh, Tasawuf, Qur'anic Tajweed, and Tafsir. Teachers at the Ummi Study Center use a variety of methods in spiritual development, including lectures, Q&A sessions, practice (memorizing and practicing prayers and recitations of Salat), as well as personal and classical approaches (addressing individual learning difficulties personally and teaching groups classically). The challenges faced in spiritual development at the Ummi Study Center include inadequate facilities, the influence of technology, lack of parental attention and supervision, and negative external influences. To overcome these challenges, solutions implemented include strengthening collaboration with parents, improving facilities and infrastructure, and increasing learning motivation. This study recommends continuously enhancing the quality of spiritual education through various innovations and collaborations among the study center, parents, and the community.